Complex Technical Management Problems At Port City Dipoles - Markos Margaritis; Maria Atzemi; Michalis Makedonas (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2023)
This study focuses on the examination of the city-port relationship from an urban planning perspective, exploring whether it can be a harmonious or a rivalry relationship and whether it can contribute to the creation of local development and national development in general. Another vital dimension considered in this study is the technical and environmental aspects that play a pivotal role in shaping the dynamics between these two entities. A port city refers to a coastal city within the boundaries of which urban and port activities are developed and carried out. Although the complexity of city port dichotomy is not captured by this definition, as it is a powerful dipole, consisting of two interdependent spatial elements, the city and the port. The strong interaction between the two creates strong spatial links that form a relationship of major importance, which has drawn considerable research attention from various fields, with urban planners in particular keenly interested in this unique category of cities